Religious Harmony Forum (FKUB): Developing religious harmony awareness village in Pesawaran District - Sinta Kustiani; Abdul Syukur; Sri Ilham Nasution (Universitas Muhammadiyah Magelang, 2023)
The purpose of this community service is to foster harmony by forming a 'Religious Harmony Awareness Village'. The method used in this program refers to the Joint Ministerial Regulations Number 8 and 9 of 2006, namely (1) providing social assistance and socializing worship regulations; (2) forming a forum for communication of interfaith leaders; (3) socialization and understanding and implementation of PBM and harmony among interfaith communities; (4) certify waqf land and land for interfaith houses of worship; (5) implementing interfaith harmony and mutual cooperation through the house renovation program, and (6) facilitating the issuance of permits to construct houses of worship. The results of this program include an increase in indicators of inter-religious harmony such as tolerance, mutual respect, and kinship in community life in Poncokresno Village. Apart from that, a mosque was also built, 4 houses were renovated, and a building construction certificate (IMB) was issued for the church.